Ortho-functionalized pyridinyl-tetrazines break the inverse correlation between click reactivity and cleavage yields in click-to-release chemistry - Ron M. Versteegen; Raffaella Rossin; Ivo A. W. Filot; Freek J. M. Hoeben; Arthur H. A. M. van Onzen; Henk M. Janssen; Marc S. Robillard (Communications Chemistry)
Abstract The bioorthogonal tetrazine-triggered cleavage of trans-cyclooctene(TCO)-linked payloads has strong potential for widespread use in drug delivery and in particular in click-cleavable antibody-drug conjugates (ADCs). However, clinical translation is hampered by an inverse correlation between click reactivity and payload release yield, requiring high doses of less reactive tetrazines to drive in vivo TCO reactions and payload release to completion. Herein we report that the cause for the low release when using the highly reactive bis-(2-pyridinyl)-tetrazine is the stability of the initially formed 4,5-dihydropyridazine product, precluding tautomerization to the releasing 1,4-dihydropyridazine tautomer. We demonstrate that efficient tautomerization and payload elimination can be achieved by ortho-substituting bis-pyridinyl-tetrazines with hydrogen-bonding hydroxyl or amido groups, achieving a.o. release yields of 96% with 18-fold more reactive tetrazines. Applied to on-tumor activation of a click-cleavable ADC in mice, these tetrazines afforded near-quantitative ADC conversion at a ca. 10- to 20-fold lower dose than what was previously needed, resulting in a strong therapeutic response.